# math

12x^2y-6xy^2/3xy

1. 👍
2. 👎
3. 👁
1. 12x^2y-6xy^2 = 3xy(4x-2y)

so, when you divide by 3xy, yo just get 4x-2y

1. 👍
2. 👎

## Similar Questions

1 Which property is used in the equation below? 12(x + 4) = 12x + 48 A Associative Property of Addition B Commutative Property of Addition C Distributive Property D Reflexive Property 2 Which expression is equivalent to 3 x – 3

2. ### Algebra problem

Multiply (x-5/4x+8)*(12x^2+32x+16) A. (3x+2)/4(x-5) B. (x-5)(3x+2)/4 C. (x-5)(3x+3) D. (x-5)(12x+8) Please help me solve this problem because all I get is 3x^2-13x-10 (which isn't a choice.)

3. ### Algebra 1

1) what is the simplified form of (x-2)(2x+3)? Use the distributive property. A) 2x^2-x-6 B) 2x^2-6 C)2x^2-7x-6 D) 2x^2 +x-6**** 2) what is the simplified form of (3x+2)(4x-3) use a table. A)12x^2+18x+6 B) 12x^2+x-6 C)

4. ### Algebra 1

A square painting is surrounded by a frame. the outside edges of the frame are x inches in length, and the frame is 3 inches thick. What is the total area of the frame? A)-12x+36 B)12x-36 C)x^2+12x+36 D)x^2-12x-36 Is it C or D?

1. ### Algebra

What is the side length of a square with an area of 144x²? A.12 B.12x C.±12x D.no solution I think it is C...?

2. ### Calculus!! HELP!!

1) The sides of the triangle shown increase in such a way that (dz/dt=1) and (dx/dt=(3dy/dx)) At the instant when x = 12 and y = 5, what is the value of dx/dt? 2) Let f(x) = x^3 − 4. Which of these is the equation for the normal

3. ### Algebra

To solve 9x^2-12x+4=49 by using the Square Root Property, you would first rewrite the equation was as A. 9x^2-12x-45=0 B.(3x-2)^2=+/-49 C.(3x-2)^2=7 D.(3x^2)^2=49

4. ### Geometry

Which equation has exactly one real solution? A 4x^2– 12x– 9 = 0 B 4x^2+ 12x+ 9 = 0 C 4x^2– 6x– 9 = 0 D 4x2+ 6x+ 9 = 0 Please teach me how to do this

1. ### math

Which linear equation represents a non-proportional relationship? A) y = 0.2x B) y = 12x C) y = −12x D) y = −12x + 5 i don't know how to do this or what it means, please help me

2. ### algebra1

could you walk-through the steps to solving this problem because I am stuck; 3x-5(3x-7)=2(x+9)+45 Let me know if you have a question in any step. 3x-5(3x-7)=2(x+9)+45 3x-15x+35= 2x+18+45 -12x+35 = 2x+63 -35 -35 -12x= 2x +63-35

3. ### Math

Is the LCD of x/2x-4 and 5x/12x-24 not 24(x-2)? The original question is x/2x-4 + 5x/12x-24 and I factored the denominators first so that I could find the LCD. And I got: x/2(x-2) + 5x/12(x-2) After that, I multiplied up to the

4. ### Simultaneous equation

X+y+z=1......(1) x^2+y^2+z^2=35........(2) x^3+y^3+z^3=97.........(3) solution but from 3 (x^3+y^3)=(x+y)^3-3xy(x+y)......(4) puting 4 into 3 bck (x+y)^3-3xy(x+y)+z^3=97.......(5) now from 1 x+y=1-z......(6) putin 6 into 7 we have